Development of ethnomathematics-integrated android-based media for enhancing problem-solving skills in secondary geometry learning - Hodiyanto Hodiyanto; Patrick Kyeremeh; Gemi Susanti; Veti Aprida; Hartono Hartono (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2026)
Mathematical problem-solving abilities among junior high school students remain persistently underdeveloped, particularly in geometry instruction on prisms and pyramids, which frequently proceeds without interactive or culturally responsive media. Although interest in ethnomathematics-informed digital tools continues to grow, empirical evidence directly linking Android-based applications grounded in local cultural heritage to measurable gains in problem-solving at this level remains scarce. This study developed an Android-based m-learning medium integrating ethnomathematical elements into prism and pyramid instruction to enhance eighth-grade students’ mathematical problem-solving skills. The 4D Model (Define, Design, Develop, and Disseminate) was applied, and a small-scale pilot trial was conducted involving ten eighth-grade students at SMP Negeri 2 Pontianak. Expert appraisal yielded a composite validity score of 95.33%, practitioner and learner evaluations produced a practicality rating of 93.95%, and effectiveness testing revealed a statistically significant improvement, with mean scores rising from 51.11 at pretest to 90.83 at posttest (p = 0.00000034; Cohen’s d = 3.09). The integration of local cultural artefacts—notably ketupat, patlau, and pengkang—effectively bridged abstract geometric concepts with students' everyday experiences. Given the pilot nature of this study, the findings should be regarded as preliminary and not yet generalisable. Future research is encouraged to involve larger, more diverse samples and to employ controlled experimental designs to validate these outcomes more rigorously.